2021
DOI: 10.3390/ijerph18062924
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation Intervention in Patients with COVID-19 after Hospital Discharge to Improve Functional Capacity and Quality of Life. Study Protocol for a Multicenter Randomized Clinical Trial

Abstract: COVID-19 can cause important sequels in the respiratory system and frequently presents loss of strength, dyspnea, polyneuropathies and multi-organic affectation. Physiotherapy interventions acquire a fundamental role in the recovery of the functions and the quality of life. Regarding the recovery phases after hospital discharge, the current evidence available is very preliminary. Telerehabilitation is presented as a promising complementary treatment method to standard physiotherapy. The main objective of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…The multicomponent programme allowed several interventions to be considered and evaluated in the virtual setting in individuals after COVID-19 hospitalisation but may have diminished the effects of any single intervention. While multicomponent telerehabilitation programmes have been proposed,10 47 48 to our knowledge, no published study has tested a supervised multicomponent telerehabilitation programme versus an active control group in individuals after COVID-19. Given our wide variety of potential interventions (table 1), substantial differences in impairments following COVID-19,1 49 and the biobehavioural approach of our study valuing participants’ autonomy and goals, the treatment programmes varied substantially among participants.…”
Section: Discussionmentioning
confidence: 99%
“…The multicomponent programme allowed several interventions to be considered and evaluated in the virtual setting in individuals after COVID-19 hospitalisation but may have diminished the effects of any single intervention. While multicomponent telerehabilitation programmes have been proposed,10 47 48 to our knowledge, no published study has tested a supervised multicomponent telerehabilitation programme versus an active control group in individuals after COVID-19. Given our wide variety of potential interventions (table 1), substantial differences in impairments following COVID-19,1 49 and the biobehavioural approach of our study valuing participants’ autonomy and goals, the treatment programmes varied substantially among participants.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying systemic inflammation contributes to muscle atrophy indirectly (lung obstruction and forced inactivity) or directly (increased muscle wasting, necrosis, fibrosis and autophagy, and mitochondrial dysfunction), while viral antigen mimicry might cause muscle denervation in peripheral nerves. While physical activity (PA) has been identified as a predictive and protective factor against severe forms of COVID-19 [ 17 , 18 , 19 , 20 ], it has also been suggested as a key factor for rehabilitation [ 21 , 22 , 23 ], both for the acute and long-term consequences of this new global disease. According to a survey questioning the specific rehabilitation needs reported by post-COVID-19 patients themselves [ 24 ], exercise guidance appears to be a primary concern.…”
Section: Introductionmentioning
confidence: 99%
“…Recent rapid advance in information and communication technologies together with wearable devices has made it possible to implement digital remote rehabilitation for patients with chronic pulmonary diseases, the efficacy and safety of which have been proven non‐inferior to those of traditional approaches 17 . Several studies have demonstrated the benefit effects of telerehabilitation in improving the physical and psychological condition among patients with COVID‐19, 15,25–27 and some studies are on the way 28,29 . More importantly, telerehabilitation can significantly increase accessibilities of medical service and reduce transmission risk of the virus.…”
Section: Discussionmentioning
confidence: 99%